S-band Brillouin erbium fibre laser - Harun, S.W.; Cheng, X.S.; Saat, N.K.; Ahmad, H. (2005)
A multi-wavelength Brillouin erbium fibre laser, which operates in short wavelength band (S-band), is proposed and demonstrated. The system employs both linear gain and nonlinear gain front a 20 in S-band erbium-doped fibre and a 500 m singlemode fibre, respectively, to generate an optical wavelength comb with spacing of approximately 0.084 nm. Two 80/20 couplers were used in the system as an internal feedback of generated Stokes signal to produce cascaded Brillouin Stokes for multiwavelength operation. A stable output laser comb of up to seven lines was obtained with a Brillouin pump of 3.5 mW and a 980 nm pump of 200 mW.